Balanço e evolução temporal de fósforo e potássio em três solos sob sistema plantio direto no Paraguai - Fois, Diego Augusto Fatecha (2010)
Soybean, corn and wheat crops occupy actually 70% of the agricultural areas of Paraguay, with increasing fertilization consumption, suggesting the necessity of an efficient use of this input. The objectives of this work were to analyze the balance and temporal evolution of phosphorus and potassium in three no-till soils from Paraguay. The experiments were carried out in Itapua, Alto Parana and Misiones departments over soils with different textures and fertility levels from 2003 to 2006. The treatments followed a random blocks design with three replications. Phosphorus treatments had five fertility creation rates of 0, 50, 100, 200, and 400 kg P2O5 ha-1 and four maintenance rates of 0, 40, 80, and 120 kg P2O5 ha-1. Potassium treatments were four rates of 0, 25, 75, and 100 kg K2O ha-1. Crop and relative yields, P and K balance and evolution in the soil were determined. Itapua and Misiones did not present response for P2O5 amendment, with the exception of Alto Parana. Itapua, Alto Parana, and Misiones did not present significant responses to K20 amendment. Soybean and corn were the major P and K extractor crops averaging 40 and 46% of the total nutrient exportation, respectively. There was correlation between crop yield and the P budget in Alto Parana and Misiones, with the exception of Itapua. There was no correlation between crops relative yields and the K budget in neither sites. At the average of the three sites the plot without fertilization decreased 2.7 and 8.7 mg dm-3 of P and K soil nutrient levels with rates of 0.6 and 1.8 mg dm-3 yr-1, respectively. P and K contents were kept constant with amendments rates of 50 kg P2O5 ha-1 and 40 kg K2O ha-1. There was the necessity to apply 11 kg P2O5 ha-1 to increase 1 mg P dm-3 of soil and extract 36.8 kg P2O5 ha-1 to decrease 1 mg P dm-3 of soil. For potassium, 3.1 kg K2O ha-1 were necessary to increase 1 mg K dm-3 of soil and extract 28.5 kg K2O ha-1 to decrease 1 mg K dm-3 of soil.